2016
DOI: 10.3390/ijms17122047
|View full text |Cite
|
Sign up to set email alerts
|

miR-429 Inhibits Differentiation and Promotes Proliferation in Porcine Preadipocytes

Abstract: MicroRNAs (miRNAs) are crucial regulatory molecules for adipogenesis. They contribute to the controlling of proliferation and differentiation of preadipocytes. Previous studies revealed an important role of miR-429 in cell invasion, migration, and apoptosis. Our previous work has shown that the expression of miR-429 in subcutaneous fat can be observed in newly born (3-day-old) Rongchang piglets rather than their adult counterparts (180-day-old). This expression pattern suggests that miR-429 might be functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 46 publications
(61 reference statements)
5
36
1
1
Order By: Relevance
“…Generally, a gene or miRNA has the opposite effect on cell proliferation and differentiation. Recent studies showed that miR-664-5p promoted myoblast proliferation and inhibited myoblast differentiation [30], and miR-429 accelerated proliferation of porcine preadipocytes and repressed adipogenic differentiation [31]. Interestingly, in this study, miR-146a-5p repressed both proliferation and differentiation of intramuscular preadipocytes.…”
Section: Discussionsupporting
confidence: 43%
“…Generally, a gene or miRNA has the opposite effect on cell proliferation and differentiation. Recent studies showed that miR-664-5p promoted myoblast proliferation and inhibited myoblast differentiation [30], and miR-429 accelerated proliferation of porcine preadipocytes and repressed adipogenic differentiation [31]. Interestingly, in this study, miR-146a-5p repressed both proliferation and differentiation of intramuscular preadipocytes.…”
Section: Discussionsupporting
confidence: 43%
“…Visible connective tissue was removed and finely minced. Intramuscular preadipocytes were isolated based on previous studies (11,30,31). In brief, muscle tissues were digested in a digestion buffer consisting of 1 mg/ml collagenase type I (Thermo Fisher Scientific) in a shaking water bath for 1.5 h at 37°C.…”
Section: Isolation Of Intramuscular Preadipocytes and Cell Culturementioning
confidence: 99%
“…According to previous reports [ 25 , 46 , 47 ], one female LiangShan Pig was sacrificed for porcine intramuscular preadipocytess isolation at three days. Briefly, Longissimus dorsi muscles (LDM) were aseptically isolated and washed three times using phosphate buffered saline (PBS, Gibco, Grand Island, NY, USA) containing 200 U/mL penicillin–streptomycin (Hyclone, Logan, UT, USA).…”
Section: Methodsmentioning
confidence: 99%